Implementation of Independent Curriculum Management in Movering Schools and Sharing Independent Schools - Pattylima, Jesika Berta; Sumual, Shelty D.M.; Krowin, Martinus M. (Abdurrauf Science and Society, 2025)
This study aims to determine the Implementation of Independent Curriculum Management at Sekolah Pengbangun and Sekolah Mandiri Panggang. This study is a descriptive study using a qualitative approach. The research location is at GMIM Ritey Elementary School and GMIM Lopana Elementary School. The techniques used in data collection are observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of this study are that GMIM Ritey Elementary School Drive School designed ATP, created teaching and assessment tools using examples from PMM, designed the P5 project by creating a project module, the implementation of the P5 project runs according to the project module, teachers have implemented differentiated learning, there is collaboration between teachers and also parents and the community, teacher and student reflections and evaluations, implementation of formative assessments during learning and summative assessments are divided into daily summative, mid-semester summative, and end-of-semester summative, remedial for students who have not achieved learning outcomes, and P5 project assessments based on the dimensions assessed and their report cards are given once a year. Independent School Sharing GMIM Lopana Elementary School made ATP and teaching and assessment tools from examples on the internet, there was no P5 project planning and the implementation of the P5 project did not go well, had not implemented differentiated learning, there was collaboration between teachers, parents and the community, teachers reflected on students by asking questions at the end of learning, formative assessments were carried out during learning by giving assignments and summative during assessments the mid-semester and end-of-semester summatives, remedial in the form of oral or written exams, and the P5 project assessment had not been realized.